The Geography of Occupational Concentration Among Low-Skilled Immigrants. Issue 2 (May 2019) - Liu, Cathy Yang; van Holm, Eric Joseph
Employment concentration among low-skilled immigrants is a well-documented phenomenon in the U.S. labor market though its temporal and spatial patterns are less well examined. With Census microdata, the authors trace detailed occupational niches from 1990 to 2010 for all immigrants, as well as Asian and Latino immigrants separately, to understand how these niches have evolved over the past two decades. Using the Herfindahl−Hirschman Index measure, the authors further capture the geographic variation in relative occupational concentration across metropolitan statistical areas and test what metropolitan-level contexts and policies help explain such differences. The authors find that metropolitan areas with larger total and immigrant populations, greater human capital, higher residential mobility, and more diverse economies have expanded low-skilled immigrants' occupational choices. Conversely, policies such as higher minimum wages and greater union membership may, in fact, increase occupational concentration, at least for some groups.